Documentation of psoriasis in routine care – expert consensus on a German data set. (7th October 2021) - Otten, Marina; Mrowietz, Ulrich; von Kiedrowski, Ralph Michael; Otto, Ramona; Altenburg, Andreas; Aschoff, Roland; Beissert, Stefan; Beiteke, Ulrike; Bonnekoh, Bernd; Hoffmann, Matthias; Körber, Andreas; Maaßen, Dirk; et al.
Summary: Background and objectives: Documenting patient data in psoriasis clinical practice can improve care, but standardized and transparent documentation is rare. The current project aimed to develop a data set for the documentation of psoriasis in daily practice. Material and methods: In four online Delphi rounds and one in‐person meeting, 27 psoriasis experts allocated variables to a standard, an optimal and an optional data set. Most of the questions were standardized. Open questions were included to allow for the provision of reasons and to enlarge the data sets. Furthermore, in the in‐person meeting we considered a) patients' attitudes and b) dermatologists' information on the current usage and acceptability in Germany. Results: The consensus approach resulted in a data set with 69 variables. The standard data set includes 20, the optimal data set 31 and the optional data set 18 variables. In summary, the data set can mainly be grouped into master data, general status and medical history data, medical history of psoriasis, status of psoriasis, diagnostics and comorbidity, therapies and patient‐reported outcomes. Conclusions: The consensus recommendation of a standard, an optimal and an optional data set for routine care of psoriasis intends to be a decision‐making aid and an orientation for both daily practice and further development of documentation systems.